Regularities in the effect of model ion irradiation on the structure and properties of vacuum-arc nitride coatings - Andreev, A.A.; Voyevodin, V.N.; Sobol, O.V.; Gorban’, V.F.; Kartmazov, G.N.; Stolbovoy, V.A.; Levenets, V.V.; Lysan, D.V. (Вопросы атомной науки и техники, 2013)
The effect of irradiation with ions Ar+ (energy of 1 and 1.8 MeV) and He+ (energy of 0.6 MeV) on the structure, microhardness and elastic modulus of the vacuum-arc nitride coatings. It is shown that the level of exposure to radiation vacuum-arc nitride coatings can be divided into 3 classes: 1) “the most structure persistent” – significant changes occur only on the substructure level (as an example – multi-element system Ti-Zr-V-Hf-Nb-Ta-N); 2) “the medium resistance “ – significant changes occur in the macro stress-strained state (as an example – the system Ti-N); 3) “structural variable” – significant changes in the macro-level and phase composition (as an example – the system Mo-N). Проведено аналіз впливу опромінення іонами Ar+ (з енергією 1 і 1,8 МеВ) і He+ (з енергією 0,6 МеВ) на структуру, мікротвердість і модуль пружності вакуумно-дугових нітридних покриттів. Показано, що за рівнем впливу іонного опромінення вакуумно-дугові нітридні покриття можна розділити на 3 класи: 1) найбільш структурно стійкі – суттєві зміни відбуваються тільки на субструктурному рівні (як приклад – багатоелементна система Ti-Zr-V-Hf-Nb-Ta-N); 2) середньої стійкості – суттєві зміни відбуваються в напружено-макродеформованому стані (як приклад – система Ti-N); 3) структурно змінювані – суттєві зміни на макроструктурному рівні і в фазовому складі (як приклад – система Mo-N). Проведен анализ влияния облучения ионами Ar+ (с энергией 1 и 1,8 МэВ) и He+ (с энергией 0,6 МэВ) на структуру, микротвердость и модуль упругости вакуумно-дуговых нитридных покрытий. Показано, что по уровню воздействия ионного облучения вакуумно-дуговые нитридные покрытия можно разделить на 3 класса: 1) наиболее структурно стойкие – существенные изменения происходят только на субструктурном уровне (как пример – многоэлементная система Ti-Zr-V-Hf-Nb-Ta-N); 2) средней стойкости – существенные изменения происходят в напряженно-макродеформированном состоянии (как пример – система Ti-N); 3) структурно изменяемые – существенные изменения на макроструктурном уровне и в фазовом составе (как пример – система Mo-N).